Dynamic Load Sharing at Domestic Level Using the Internet of Things - Rashid, Faizan; Ahmad, Raza; Muhammad Talha, Hafiz; Khalid, Arslan (International Journal of Integrated Engineering, 2020)
At the domestic level, load management plays a vital role as the consumer line gets overloaded due to the various load categories. The fully loaded line consumes more energy units, which increases the electricity bill of the consumer. To circumvent the issue of load unbalancing, an automated load management system is developed that shifts the load from one line to another. The proposed system is developed by making use of current and potential sensing transformers and the Arduino Mega board. Moreover, the proposed system also provides an internet of things (IoT) based monitoring facility to the user. The sensed information from the system is uploaded to the webserver with the help of Wireless Fidelity (Wi-Fi) from where the user can access this information at any time through appropriate applications. Based on the monitoring data, the user can take necessary decisions regarding switching off unnecessary load. Both simulation and hardware results demonstrate the effectiveness of the proposed system.